(untitled) (Experimental biology, 2018)
The genus Astragalus L. (Galegeae, Fabaceae) – the largest genus of flowering plants, consisting of about 2500-3000 species, prevailing in Northern Hemisphere. Species diversity research of the genus is of significant interest for understanding of process of genesis and evolution of Eurasia steppe flora. The work provides a comprehensive analysis of the largest genus of Aktobe flora region - Astragalus L., represented by 50 species amounting to 3,8 % of the total number of flora species. Systematic analysis of the genus Astragalus L. identified a dominance of subgenus Cercidothrix represented by 16 sections combining 37 species or 74% ot the total number of astragalus and small number of the subgenus Phaca, represented by 4 sections with 5 species.Life forms spectrum study of environmental types in relation to substrate moisture according to I.G. Serebryakov, C. Raunkiaer showed steppe nature of flora and it’s specificity. Natural habitat analysis of astragalus species of Aktobe flora region revealed 22 types of habitats with predominance of Zavolzhsk – Kazakhstan, Zavolzhsk-Kazakhstan-Turan, Turan types. The species of the genus Astragalus L. are represented by 2 habitat groups: Euro-Asian steppe and earlymediterranean. 10 disjunctive natural habitat species with obvious dominance of meso-disjunctive group were identified in the genus Astragalus L. of Aktobe flora region. The group of endemic species is represented by Astragalus aktiubensis, Astragalus mugodsharicus, Astragalus temirensis, Astragalus subarcuatus, amounting to 8,0 % of the total number of the genus species. Species distribution of the genus Astragalus L. identified a predominance of psammophilous floristic complex (22 species) and steppe floristic complex (21 species). Key words: genus, flora, astragalus, natural habitat, disjunction, floristic complex.